PENGEMBANGAN VIDEO ANIMASI PENUNTUN EKSPERIMEN DENGAN MENGGUNAKAN APLIKASI POWTOON PADA MATERI MOMENTUM DAN IMPULS KELAS X SMA - Mar’atul Masruroh; Muhammad Nasir; Naila Fauza (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article focuses on the development of an experimental guide animation video using the Powtoon application on Momentum and Impulse material in class X of SMA. It was designed to produce a valid experimental guide for animation video media and was worthy to be used as learning media in the classroom. Type of the study was Research and Development with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Quantitative data were validity values from the animated video of the experimental guide and qualitative data wereobtained from the validator’s comments and suggestions. The instrument used was the validation sheet of the animation video. The data were analyzed descriptively to determine the validity of the experimental guide animation video using Aiken's V formula. The results of the study indicated that the average value of Aiken's V validity index in the design aspect was 0.813, the pedagogical aspect was 0.845, the content aspect was 0.887, and the technical aspect was 0.795. The overall result of the average validity index value of Aiken's V was 0.834, in which the validity index value ofAiken's V has an indicator value of 0.40, hence it was declared as valid. Thus, it could be concluded that the experimental guide animation video using the Powtoon application on Momentum and Impulse material in class X of SMA was valid based on the design, pedagogical, content, and technical aspects.